Development of soy protein isolate emulsion gels as extrusion-based 3D food printing inks: Effect of polysaccharides incorporation - Yu, Jie; Wang, Xue-ying; Li, Dong; Wang, Li-jun; Wang, Yong (Food hydrocolloids, 2022)
Soy protein isolate (SPI) emulsion gel inks with polysaccharides of guar gum (GG) or xanthan gum (XG) for extrusion-based three-dimensional (3D) printing were investigated. The effects of the polysaccharide type and concentration on the printability, rheological properties, and microstructure of inks were discussed. Results indicated that the 3D printed products of SPI-GG0.5 inks demonstrated low dimensional printing deviation with great self-supporting capability and smooth and slightly flawed surface texture, while SPI-XG0.5 inks had the highest hardness and rough surface texture. The results of small amplitude oscillatory shear (SAOS) and large amplitude oscillatory shear (LAOS) test proved that SPI-XG0.5 inks exhibited the maximal gel strength, providing its 3D printed products with highest hardness. Secondary loops of Lissajous plots wouldn't emerge in SPI-XG0.5 inks, indicating decreased network flexibility and slightly larger dimensional printing deviation. The microstructure and fourier transform infrared (FTIR) analysis suggested the interaction of SPI with XG was stronger than that of GG due to hydrogen bonding and electrostatic interactions. When the XG concentration reached 0.5%, the network structure of the inks was changed, resulting in a rough surface texture of the 3D printed product. There are few studies on 3D printing of SPI emulsion gels, and this research offers more possibilities for the development of 3D printing inks. [Display omitted] •Adding polysaccharides to SPI emulsion gel was beneficial for printability and rheological properties.•The gel strength of SPI-XG inks was stronger than SPI-GG inks at same concentration.•SPI-GG0.5 inks' 3D printed products had the lowest dimensional printing deviation.•The surface texture of SPI-GG0.5 inks was smoother than that of SPI-XG0.5 inks.•LAOS rheology confirmed high network strength with poor flexibility of SPI-XG0.5 inks.